The use of environmental isotopes in groundwater flow study in the unsaturated zone of the Selniška Dobrava coarse gravel aquifer (Slovenia) - Mali, Nina; Urbanc, Janko (Geologija, 2006)
The knowledge about water flow and transport properties in the unsaturated zone is becoming an important predisposition for groundwater protection. The water flow and transport processes were studied in a field laboratory - a lysimeter in the coarse gravel aquifer of Selniška Dobrava, using isotope methods. The δ18O isotope values were measured monthly in the sampled unsaturated zone water and precipitation during the long-term period from 2001 to 2005. The isotope oscillations in the measuring points show that the δ18O seasonal effect in precipitation can be observed in the unsaturated zone with some delay in peak and with amplitude reduction with depth. Mean residence times of the water in the unsaturated zone were modelled with the FLOWPC 3.1 Computer package. The estimation of water flow velocity in the Selniška Dobrava coarse gravel unsaturated zone by lumped-parameter (LP) models is 0.015 m/day. The estimation of water mean residence time at lysimeter location is 5 years, i.e. in the range of 3.8-9.4 years. The research confirmed that the isotope methods are suitable tools for water flow tracing in the coarse gravel unsaturated zone, and that lumped-parameter models can be used to estimate water mean residence time in the unsatuarated zone.